2015
DOI: 10.2340/16501977-1965
|View full text |Cite
|
Sign up to set email alerts
|

Participation and quality of life outcomes among individuals with earthquake-related physical disability: A systematic review

Abstract: To maximize our understanding of quality of life and participation in injured earthquake survivors, future research should consider both the functional consequences of the injury and the environmental impact of the earthquake. The research should be based on representative samples of the injured earthquake survivors and use validated condition-specific outcome measures that are clearly defined within the publications. In addition, research should include all countries that are affected by earthquakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Lastly, as regards society, the Organization for Economic Co-operation and Development (OECD) high-level policy forum entitled Sickness, Disability, and Work [21] emphasized that the work participation of people with disabilities impacts the overall economy in a positive manner. As Nunnerley and colleagues [22] underscored, increasing employment chances for working-aged people with disabilities may improve their wellbeing status and thus reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, as regards society, the Organization for Economic Co-operation and Development (OECD) high-level policy forum entitled Sickness, Disability, and Work [21] emphasized that the work participation of people with disabilities impacts the overall economy in a positive manner. As Nunnerley and colleagues [22] underscored, increasing employment chances for working-aged people with disabilities may improve their wellbeing status and thus reduce health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of universal design and accessibility are not the only factors that increase the disaster risk for persons with disabilities; cultural attitudes, stigma and barriers to their full participation in society have the same impact. This was shown in a UN survey conducted in 126 countries, which found that only 14 per cent of people with disabilities had been consulted about disaster risk management in their communities, implying that their risk reduction needs have been ignored (United Nations Office for Disaster Risk Reduction, 2013; Hunt et al, 2015;Nunnerley et al, 2015;Stough and Kang, 2015;Skøt et al, 2016). This is particularly worrying given that, as a result of climate change, the number of disasters is expected to increase over the next few years (United Nations Refugee Agency, 2017), and therefore the disaster needs of older people and persons with disabilities should be urgently addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Sedentary life style and decreased level of physical activity during curfew and lockdown related to COVID-19 might contribute to decreased quality of life among different population (3,11). Studies have documented drop in quality of life and escalation in mental health symptoms during natural disasters (such as earthquakes), wars, and health pandemic (12).…”
Section: Introductionmentioning
confidence: 99%